Variáveis de desempenho para hospitais sem fins lucrativos - Deborah Mara Siade Barbosa (2017)
Research on the measurement of company performance aim development of metrics that are capable of contemplating all dimensions of organizational performance, since there is a consensus that a use of isolated performance indicators alone can not capture a whole complexity of the organizations. This context is even more complex when the performance to be evaluated from a non-profit hospital, due to its operational complexity and the need to congregate interests of diverse stakeholders. The context that presents itself is a shortage of resources in Brazilian health, in general, together with an increase in initiatives of transparency in organizations and indications, by the academy, of management problems in the hospitals. The aim of this research was to analyze the determinant variables of performance for Brazilian non-profit hospitals, considering the economic-financial and operational dimensions of these organizations. In order to do so, we used firm theory, stakeholder theory and agency theory as a theoretical framework, in view of the ability to relate to understand the relationships between the various stakeholders and their often irreconcilable interests in relation to performance of hospital organizations. Data were collected economic-financial and operational data from 50 non-profit hospitals, considering the period from 2006 to 2015. These secondary data were used to create a performance index, using the principal components analysis, which includes the dimensions economic-financial and operational. The aim was to construct a metric that adds more than one dimension to evaluate the performance of these institutions. The results indicate that the dimensions have very low and negative bivariate correlation among them, shedding light on the need for studies that encompass multidimensional metrics, capable of comprehending and evaluating hospitals in a broad and effective manner. The main contribution of this study is to provide the various stakeholders with the possibility to monitor and evaluate the performance of the organization in a transparent way, minimizing the agency problem, through self evaluation, and evaluate the performance of organizations comparatively.